O potrzebie szczęśliwego rodzica dla dzieci z zaburzeniami rozwoju. Relacyjno-rozwojowe podejście do wczesnego wspomagania rozwoju - Stec, Maria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article presents the most important aspects of the relational-developmental approach to early childhood development support together with the main theoretical foundations of this approach. The happy parent in his/her natural function is shown to be crucial in supporting the development of children with developmental disorders. The difficulties of the parent in communicating with a child with developmental disorders as well as desirable parenting behaviours and states that serve the child`s development are discussed. In particular, the role of play and parental attunement to the child`s behaviour was highlighted so that the child can experience a strong positive connection with his or her parent. The final section discusses the characteristics and interventions of early intervention professionals for parents of children with developmental disorders.
Keywords: wczesne wspomaganie rozwoju; relacja rodzic-dziecko; dziecko z zaburzeniami rozwoju; zabawa; wspieranie rodzica; early childhood suport; relation parent - child; children with developmental disabilities; play; supporting the parent